Π‐Ruthenium Complexes of Hexaphyrins(1.1.1.1.1.1): A Triple‐Decker Complex Bearing Two Ruthenoarene Units. (8th May 2019) - Nakai, Akito; Ishida, Shin‐ichiro; Soya, Takanori; Osuka, Atsuhiro
Abstract: Ruthenium(II) π‐coordination onto [28]hexaphyrins(1.1.1.1.1.1) has been accomplished. Reactions of bis‐Au III and mono‐Au III complexes of hexakis(pentafluorophenyl) [28]hexaphyrin with [RuCl2 ( p ‐cymene)]2 in the presence of NaOAc gave the corresponding π‐ruthenium complexes, in which the [( p ‐cymene)Ru] II fragment sat on the deprotonated side pyrrole. A similar reaction of the bis‐Pd II [26]hexaphyrin complex afforded a triple‐decker complex, in which the two [( p ‐cymene)Ru] II fragments sat on both sides of the center of the [26]hexaphyrin framework. Abstract : Die Ruthenium(II)‐Komplexierung von Bis‐ und Mono‐Au III ‐[28]Hexaphyrinen ergibt Sandwich‐Komplexe mit einer Ruthenoaren‐Einheit am seitlichen Pyrrol. Andererseits führt die Ru II ‐Komplexierung bei einem Bis‐Pd II ‐[26]Hexaphyrin zu einem Tripeldeckerkomplex mit zwei Ruthenoaren‐Einheiten auf den beiden Seiten des zentralen [26]Hexaphyrin‐Gerüsts.